Anti-windup-like Compensator Synthesis for Discrete-Time Quantized Control Systems. Issue 25 (2022) - Alsamadi, Samer; Ferrante, Francesco; Tarbouriech, Sophie
Abstract: This paper addresses the problem of designing an anti-windup like compensator for discrete-time linear control systems with quantized input. The proposed compensator provides a correction signal proportional to the quantization error that is fed to the controller. The compensator is designed to ensure that solutions to the closed-loop systems converge in finite time into a compact set containing the origin that can be tuned by the designer. A numerically tractable algorithm with feasibility guarantees is provided for the design of the compensator. The proposed results are illustrated on an academic example and an open-loop unstable aircraft system.